2020
DOI: 10.1021/acsomega.9b04403
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architect: A User-Friendly Workflow for Virtual Screening

Abstract: Computer-assisted drug design (CADD) methods have greatly contributed to the development of new drugs. Among CADD methodologies, virtual screening (VS) can enrich the compound collection with molecules that have the desired physicochemical and pharmacophoric characteristics that are needed to become drugs. Many free tools are available for this purpose, but they are difficult to use and do not have a graphical user interface. Furthermore, several free tools must be used to carry out the entire VS process, requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…In order to enhance the success rate of this virtual screening (VS) campaign, 2D approaches were discarded due to their intrinsic limitations and 3D methods were employed since they are more sensible and retain information [42]. Furthermore, a consensus analysis was performed in each step (LB and SB) to select the most promising compounds [43].…”
Section: Resultsmentioning
confidence: 99%
“…In order to enhance the success rate of this virtual screening (VS) campaign, 2D approaches were discarded due to their intrinsic limitations and 3D methods were employed since they are more sensible and retain information [42]. Furthermore, a consensus analysis was performed in each step (LB and SB) to select the most promising compounds [43].…”
Section: Resultsmentioning
confidence: 99%
“…As such, we recommend that future, more focused, research continue our docking simulations by including target baits (to reflect the limitations of false-positive and false-negative results), considering solvent effects, flexible docking, and comparing multiple docking tools. To this end, we indicate the robust docking methodologies employed in [ 68 , 81 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…40,41 As the enzymes were prepared, the molecular docking protocol was started. Thus, to evaluate the ability of the algorithm to predict possible ligand orientations, re-docking calculations were performed using the MolAr software, 42 with the implementation of the AutoDock Vina program. 43 As such, the values extracted from RMSD (5R82 = 0.94 Ǻ / 3H5Y = 1.55 Ǻ) indicated that Vina was able to predict the conformation that the co-crystallized ligands adopted experimentally within the SARS-CoV-2 M pro active site and SARS-CoV-2 RdRp polymerase.…”
Section: CLmentioning
confidence: 99%
“…56 The molecular docking was conducted with the tool AutoDock Vina (version 1.1.2), 43 as implemented in the MolAr (Molecular Architecture) software. 42 For the crystallographic M pro and RdRp polymerase structures preparation, the loop regions were rebuilt using the Modeller. 57 As such, the ions and water molecules were removed from the original PDB, with the exception of water molecules that were in the M pro and RdRp active sites.…”
Section: CLmentioning
confidence: 99%